Performance of three commercial lipases in a model enzyme modified cheese system : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Food Technology at Massey University - Gunaratne, Jagath Thusitha Kumara (Massey University, 1999)
The effects of Amano 'R' (from Penicillium roqueforti), Palatase (from Mucor miehei) and kid lipase (from kid goat) activity on hydrolysis of triglycerides in a constant enzyme modified cheese (EMC) base have been investigated. The effects of incubation time, temperature, enzyme concentration, pH, water activity (a w ) and salt-in-moisture content on enzyme activity were studied. Under the same conditions (0.15% enzyme, 30°C, 24 h), Palatase and Amano 'R' showed a greater extent of hydrolysis (total free fatty acids) than Kid lipase. The total free fatty acids (FFAs) released by Palatase, Amano 'R' and Kid lipase were 224, 188 and 20.5 mmol FFA. kg EMC. -1 , respectively. The optimum temperature for hydrolysis by Amano 'R', Palatase and Kid lipase was around 30°C, 55°C and 45°C respectively. Amano 'R' was very heat sensitive, compared to the other two enzymes. Hydrolysis increased with increasing initial pH. The optimum pH's determined for Amano 'R', Palatase and Kid lipase were 7.5, 8.0 and 5.5 respectively. Enzyme activity decreased slightly as water activity decreased and salt-in-moisture content increased, for all enzymes. The incubation time and enzyme concentration showed the expected trend. At all process conditions, a high percentage (about 55%) of the fatty acids released by kid lipase was butyric acid. Both Palatase and Amano 'R' were relatively non selective and released large amounts of all fatty acids. Compared to Palatase, Amano 'R' selectively released a higher percentage of butyric acid (about 15% compared to 10%). Generally, the rate of release of butyric acid was greater at lower incubation temperatures for all enzymes. Also, the percentage of butyric acid release decreased with increasing initial pH for Palatase lipase.
Keywords: Lipase; Cheese -- Microbiology; Enzymes -- Industrial applications